Social Economy movements in zones of armed conflict in Mexico - Castillo Romero, Nadia Eslinda (DIXI, 2020)
Objectives: This article derives from the initial reflection embodied in the book Economía Social en contextos de violencia: México y Colombia. The objective of this project was to train social economy counselors who would contribute to the generation and accompaniment of Social Economy companies in historically impoverished areas now rife with drug trafficking so that, through community work, they could undertake solidarity tools that would contribute to social pacification.Methodology: The first results of the project “Strengthening economic projects in territories of high vulnerability and situations of violence” were observed, which was carried out by the Economic and Social Innovation Laboratory (laines) of the Universidad Iberoamericana Puebla, México in 2017. The case of Tancítaro and Cherán in the Mexican state of Michoacán is addressed.Findings: We observe that economic autonomy through the generation of experiences and social economy circuits is a long-term process.
Keywords: Cherán; peace building; social economy; Tancítaro; violence